Study of Structure and Magnetic Properties of SmCo10 Alloy Prepared by Different Methods - Xiang Chi; Ying Li; De-quan Er; Xu-hao Han; Xiu-li Duan; Ji-bing Sun; Chun-xiang Cui (Advances in Materials Science and Engineering)
In this paper, the phase compositions, microstructures, atomic structures, and magnetic properties of Co-rich SmCo10 alloys prepared by arc-melting, annealing, and melt-spinning were studied. It was found that as-cast alloy is composed of Th2Zn17-type Sm2Co17 matrix with an average grain size of ∼45 μm accompanied by lamellar eutecticum (consisting of α-Co and Th2Zn17-type Sm2Co17) distributed at grain boundaries. The annealed alloy has the same phase composition and phase distribution as the as-cast alloy except that the average grain size decreases to ∼35 μm, and the eutecticum has more homogeneous distribution on the matrix. Simultaneously, the atomic structure of Sm2Co17 is unchanged with only a decrease in structural disorder after annealing. The as-spun ribbons are composed of ∼95.5 vol.% TbCu7-type Sm2Co17 and the rest α-Co. The short rod-shaped α-Co grains are intermittently distributed at the grain boundaries of equiaxed Sm2Co17 grains. The as-spun ribbons show a higher coercivity, and the annealed alloy shows maximum magnetization. The structural parameters were calculated by Extended X-ray Absorption Fine Structure (EXAFS), and the relationship between structure and magnetic properties was discussed in detail.